(3JYdjbI Ydi TQM GdTQhGfj Ydi BOGH GdHMKs - (3TGg MSjf LdHj GdGeGSj (B((3, (B918 (3g`(B)s ((3aj HdOI BeOs)
(3ChdgG (B:s
(3GYde Cf Hjf GdMeO hGdefI aQbG ef LeGYI Cf GdMeO jYe (B... (3GdaVGFd hGdahGVd hGdefI jNU GdahGUd adGHO dYOhd (B..(3Yf GdaGVd GdeTghQI Edi GdeaVhd GdZjQ GdeTghQ ef fcJg hdYd GdfcJI gj Cf (B...s
(3BNQgG (B:s
.. (3aj UOQ GdcdGe HeYfi GdehLhO aj GdNGQL ShGA ef JYOOJ ajgG GdCchGf Ch JMOOJ GdCYUGQ Ch dG (B.. (3jUOb Ydi eG cGf ajS Cf GdMOhK (B.. (3ceG dG jNai Ydi GdeJCed GdPcQ (B. (3JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf (B1\40s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdadSaI hGdefWbs